Positive charges of the initial C-terminus domain of Cx32 inhibit gap junction gating sensitivity to CO2. - Wang, X G (1997)
Gap junction channels close with CO2 exposure. To determine whether the carboxy-terminus (CT) of connexin32 (Cx32) participates in gating, the CO2 sensitivity of channels made of Cx32 or Cx32 mutants was studied by double voltage clamp. In Xanopus laevis oocytes expressing Cx32, junctional conductance (Gj) dropped to 85% and 47% of controls with 3- and 15-min CO2 exposures, respectively. In response to the 15-min exposure to CO2, pHi dropped to approximately 6.4 in 5-7 min and did not decrease further, even with 30-min exposures. CT deletion by 84% did not affect CO2 sensitivity, but replacement of five arginines (R215, R219, R220, R223, and R224) with asparagines (N) or threonines at the beginning of CT (CT1) in Cx32 or Cx32 deleted beyond residue 225 greatly enhanced CO2 sensitivity (with 3-min CO2 Gj dropped to approximately 8%). Partial R/N replacement resulted in intermediate CO2 sensitivity enhancement. R215 is a stronger inhibitor than R219-220, whereas R223-224 may diminish the inhibitory efficiency of R215 and R219-220. Therefore, positive charges of CT1 reduce the CO2 sensitivity of Cx32, whereas the rest (> 80%) of CT seems to play no role in CO2-induced gating. The role of presumed electrostatic interactions among Cx32 domains in CO2-induced gating is discussed.